Evaluating the Influence of Isometric Exercise on Blood Pressure and Intraocular Pressure in Healthy Subjects - Mukesh Kumar; Uzma Rafeeq; Sayanti Bosu; Lokesh Chauhan (Delhi Journal of Ophthalmology)
Purpose: This study aimed to investigate the temporary changes in systemic blood pressure and intraocular pressure (IOP) induced by isometric exercise. Design: Interventional comparative design. Methodology: The study included 70 participants (mean age: 21.21 years, 54.3% female, 45.7% male) who performed isometric exercise using a handgrip dynamometer. Resting IOP was recorded before the exercise. The exercise protocol involved 20 squat exercises followed by the hand grip exercise. Participants sustained the handgrip with their dominant hand until they could no longer maintain the exertion. IOP was measured during the exercise and at 2, 5, and 10 min after the exercise, first in the right eye and then in the left eye. Blood pressure, heart rate, and oxygen saturation levels were also measured at different time points. Results: Pulse rate and oxygen saturation levels showed significant differences between baseline and after 15 min of exercise. The mean IOP exhibited a significant decrease from baseline to 2, 5, and 10 min of exercise, while no significant change was observed between 5 and 10 min. Conclusion: Isometric exercise induces temporary changes in IOP and systemic blood pressure. Significant decreases in IOP were observed at 2, 5, and 10 min of exercise, with no further change between 5 and 10 min. Pulse rate and oxygen saturation levels showed significant differences after 15 min of exercise. Further research is needed to explore long-term implications and potential risks.